PERANCANGAN ROBOT PEMADAM API DENGAN PENGONTROLAN GERAK METODE PROPORTIONAL INTEGRAL DERIVATIVE (PID) MENGGUNAKAN SENSOR SONAR BERBASIS MIKROKONTROLLER - Sondang Sibuea; Agung Rahmaddoni; Yohanes Bowo Widodo (Pusat Riset dan Inovasi Nasional, 2021)
This research designs and implements a control algorithm on a wheeled wall follower robot that uses a PID controller (Proportional, Integral, Differential) as a navigation system for a wall follower fire fighting robot. The task of this robot is to walk along the walls of the area. The PID controller aims to smooth the movement of the robot when tracing the track space. With the help of the PID controller, the wall follower robot is able to navigate safely, smoothly, responsively and quickly. Fire fighting robots require a variety of sensors to run properly, one of which is using sonar sensors that are used for robot navigation. This sensor works based on the principle of wave reflection, where in this case the variable measured is the time of reflection since the wave was emitted. The sonar sensor detects an obstruction. The robot will turn and walk again without hitting obstacles or objects in the vicinity. To detect fire, fire sensor is used. This sensor also find hotspots by assessing the intensity of the light. Arduino ATMega328 microcontroller functions as a robot control. The output of the microcontroller will produce logic 1 to activate the motor driver to activate the right and left wheel motors. The DC motor is used as a driving force for the robot, and the battery here functions as a power supply for the robot. The result is, this robot can detect the fire point of the candle and extinguish the candle flame.